STRATEGI PENINGKATAN INDEKS PENDIDIKAN MELALUI ALOKASI BELANJA PEMERINTAH DAERAH BIDANG PENDIDIKAN DI PROVINSI JAWA TIMUR - Mahendra, Roy; Fariyanti, Anna; Falatehan, A. Faroby (Jurnal Manajemen Pembangunan Daerah, 2016)
Education is an important investment to improve regional competitiveness in the future. One indicator of the successful development in education is the education index. The objectives of this study were (a) to identify the factors that influence the education index in the East Java province, (b) to formulate a strategy that can increase the index education in the East Java province. The data used in this study are secondary and primary types. The data was analyzed using multiple regression analysis of the panel data and Analytical Hierarchy Process (AHP) analysis. The results showed that factors that significantly affected the education index in East Java positively were these variables: the allocated local government spending in education, income per capita, junior high school enrollment rate, senior high school enrollment rate, and the student-teacher ratio in elementary schools. The first priority of strategy based on AHP to increase the education index of East Java is equal distribution in the quantity of educators.  ABSTRAKPendidikan adalah investasi penting untuk meningkatkan daya saing daerah di masa yang akan datang. Salah satu indikator keberhasilan pada sektor pendidikan adalah indeks pendidikan. Tujuan dari kajian ini adalah (a) mengidentifikasi factor-faktor yang mempengaruhi indeks pendidikan di Provinsi Jawa Timur, (b) memformulasikan strategi untuk meningkatkan indeks pendidikan di Provinsi Jawa Timur. Data yang digunakan dalam kajian ini adalah data sekunder dan data primer. Analisis yang digunakan adalah analisis regresi berganda data panel dan Analytical Hierarchy Process (AHP). Hasil analisis menunjukkan bahwa faktor-faktor yang secara signifikan dan positif mempengaruhi indeks pendidikan di Jawa Timur adalah: alokasi belanja pemerintah daerah bidang pendidikan, pendapatan per kapita, Angka Partisipasi Sekolah tingkat SMP, Angka Partisipasi Sekolah tingkat SMA, dan rasio murid-guru tingkat SD. Prioritas strategi pertama untuk meningkatkan indeks pendidikan di Jawa Timur berdasarkan analisis AHP yaitu pemerataan kuantitas tenaga pendidik.